Future wave climate change under global warming : Ensemble projections - Lemos, Gil (2021)
Waves at the ocean surface are responsible for modulating the exchange of radiation, heat, mass and momentum between the atmosphere and the ocean. Waves also play an important role in engineering and environmental related issues, such as coastal erosion, coastal flooding, and sea level extremes, representing a major hazard for any offshore structure or operation. The impact of climate change on ocean waves is therefore of paramount importance. This thesis investigates projected changes in future wave climate as a response to global warming, through a large set of simulations (ensembles), towards the end of the 21st century. The wave climate ensembles are subjected to a strict evaluation process, through comparison with reanalyzes, hindcasts and in-situ observations, to ascertain their ability to simulate the historical wave climate. Bias correction methods are implemented, to deal with the systematic errors found between the simulated and reference data sets, ultimately generating new ensembles of bias corrected wave climate projections. Results indicate clear and statistically significant climatic change signals across vast areas of the global ocean, for several wave-related parameters, such as the significant wave height (HS), mean wave period, mean wave direction and wave energy flux. The future behavior of the HS in the North Atlantic Ocean is investigated in detail, as it shows statistically significant projected decreases, opposite to the global mean positive projection. A statistical classification method is employed to assess the evolution of the weather patterns there and relate them with the HS projections. Results indicate that atmospheric blocking and positive North Atlantic Oscillation patterns are projected to become more frequent in the future, together with a poleward displacement of the storm tracks, where the open ocean area for wave generation by the wind is smaller. Finally, the propagation of climate change through swell waves is quantified, from the wave generation areas towards the swell arrival locations, using a swell tracking algorithm to identify and trace swell events and its characteristics. It is shown that the effects of climate change on the mean close to surface wind speeds where waves are originated can be felt thousands of kilometers away, and that areas exposed to swell waves from different generation areas are often projected to suffer unbalanced HS projected changes when the direction of the incident waves is considered.